Impact of Revised Vaccination Recommendations for Mature Infants on Premature Infants’ Vaccination Compliance in Germany - Felicitas Kühne; Christof von Eiff; Julia Schiffner-Rohe; Lina Döring; Kathrin Gerchow; Karolin Seidel; Maren Laurenz (Infectious Diseases and Therapy)
Abstract Introduction The German Standing Committee on Vaccination (STIKO) changed the vaccination schedule for mature infants from a 3 + 1 to a 2 + 1 schedule for pneumococcal conjugate vaccines (PCV) in August 2015 and for hexavalent vaccines (HEXA) in August 2020. A 3 + 1 schedule is still recommended for premature infants for both vaccinations. This study analyzed the impact of the changed recommendations of PCV and HEXA vaccination on the vaccination compliance and adherence of premature infants. Methods A retrospective claims data analysis was conducted using the InGef Research Database. The study population included all premature and mature infants born in 2013, 2016, 2018, and 2020 with an individual follow-up of 24 months. Premature infants were identified by ICD-10-GM codes P07.2 and P07.3. Documented records of vaccinations were assessed in the outpatient setting. Full vaccination rates of PCV and HEXA vaccination according to STIKO recommendations, valid in the respective observational year and maturity of birth, were analyzed. Results After the change in STIKO recommendations in 2020, the full HEXA vaccination rate for premature infants decreased significantly to 57.8% (2018, 71.0%), while it increased to 81.3% (2018, 73.8%) for mature infants. A similar pattern was observed during the transition from a 3 + 1 to a 2 + 1 PCV vaccination schedule among mature infants comparing birth cohorts 2013 (premature 65.4% vs mature 68.3%) and 2016 (premature 40.8% vs mature 75.6%). Conclusion Despite the continued recommendation for a 3 + 1 PCV and HEXA vaccination schedule in premature infants, a significant decrease of completed immunization was observed for both vaccines following the adjusted recommendations for mature infants. These findings underscore the need for enhanced efforts to promote adherence to STIKO guidelines to safeguard this vulnerable population of premature infants.